PROFITABILITY INDEX DALAM FINANCIAL DISTRESS MITIGATION STUDI PADA BANK BUMN DI INDONESIA - Didi Rahmat (Jurnal Ekonomi Integra, 2019)
The results of empirical analysis of four state-owned banks in Indonesia that are included in the healthy qualifications according to the OJK and listing on the stock exchange. Using the Trend analysis method of the Indexability Data Index for the period of 2015 to 2018, it was found that; Operating Profit Margin, Net Profit Margin and Return On Assets have a positive but not significant trend, but this forms the pattern of Operating Profit Margin Growth growing significantly in the 2017-2018 period. This is inversely proportional to Total Asset Growth which experiences a negative trend. Besides that, other important things are known that the implemented financial policies form financial distress mitigation in the trend pattern of upper and lower limits for safe profitability index ratios for the four banks.